Coordination and trade‐offs among hydraulic safety, efficiency and drought avoidance traits in Amazonian rainforest canopy tree species. Issue 3 (19th February 2018) - Santiago, Louis S.; De Guzman, Mark E.; Baraloto, Christopher; Vogenberg, Jacob E.; Brodie, Max; Hérault, Bruno; Fortunel, Claire; Bonal, Damien
Summary: Predicting responses of tropical forests to climate change‐type drought is challenging because of high species diversity. Detailed characterization of tropical tree hydraulic physiology is necessary to evaluate community drought vulnerability and improve model parameterization. Here, we measured xylem hydraulic conductivity (hydraulic efficiency), xylem vulnerability curves (hydraulic safety), sapwood pressure–volume curves (drought avoidance) and wood density on emergent branches of 14 common species of Eastern Amazonian canopy trees in Paracou, French Guiana across species with the densest and lightest wood in the plot. Our objectives were to evaluate relationships among hydraulic traits to identify strategies and test the ability of easy‐to‐measure traits as proxies for hard‐to‐measure hydraulic traits. Xylem efficiency was related to capacitance, sapwood water content and turgor loss point, and other drought avoidance traits, but not to xylem safety ( P 50 ). Wood density was correlated ( r = −0.57 to −0.97) with sapwood pressure–volume traits, forming an axis of hydraulic strategy variation. In contrast to drier sites where hydraulic safety plays a greater role, tropical trees in this humid tropical site varied along an axis with low wood density, high xylem efficiency and high capacitance at one end of the spectrum, and high wood density and low turgor loss point at the other.